2018
DOI: 10.3390/polym10060612
|View full text |Cite
|
Sign up to set email alerts
|

Chirality Construction from Preferred π-π Stacks of Achiral Azobenzene Units in Polymer: Chiral Induction, Transfer and Memory

Abstract: Abstract:The induction of supramolecular chirality from achiral polymers has been widely investigated in composite systems consisting of a chiral guest, achiral host, and solvents. To further study and understand the process of chirality transfer from a chiral solvent or chiral molecules to an achiral polymer backbone or side-chain units, an alternative is to reduce the components in the supramolecular assembled systems. Herein, achiral side-chain azobenzene (Azo)-containing polymers, poly(6-[4-(4-methoxypheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…(The trans-azopolymer melting point is 80°C.) Previous studies of polymers with similar azobenzene side-chain structures in trans states have reported glass-transition temperatures in the range of 35 < T g < 80°C (29)(30)(31). We note that similar large shifts in T g as a function of isomer state have been previously observed in polybutadiene (ΔT g ∼ 90°C) (32) and azobenzene functionalized polymers (ΔT g ∼ 60°C) (21).…”
Section: Significancesupporting
confidence: 85%
“…(The trans-azopolymer melting point is 80°C.) Previous studies of polymers with similar azobenzene side-chain structures in trans states have reported glass-transition temperatures in the range of 35 < T g < 80°C (29)(30)(31). We note that similar large shifts in T g as a function of isomer state have been previously observed in polybutadiene (ΔT g ∼ 90°C) (32) and azobenzene functionalized polymers (ΔT g ∼ 60°C) (21).…”
Section: Significancesupporting
confidence: 85%
“…Furthermore, the chirality of Azo-polymers can be disrupted by UV light irradiation, and dynamically recovered by visible light irradiation or temperature regulation owing to the reversible trans - cis - trans isomerization. Thus, the chiral-achiral chiroptical switches can be achieved based on the reversible trans - cis isomerization of Azo building blocks [ 137 ]. In this section, we will mainly discuss the construction of chirality in the side-chain photochromic Azo-polymers by postpolymerization self-assembly.…”
Section: Supramolecular Chirality Of Azo-polymers Constructed By Pmentioning
confidence: 99%
“…The results of CD and UV-vis spectra suggested that the internal structures and external stimuli have distinctive influences on the induction and regulation of supramolecular chirality of achiral Azo-polymers. Recently, we used the same Azo-polymer 20 and successfully yielded CD-active Azo-polymer films triggered by chiral limonene vapor [ 137 ]. Chiroptical induction, switching, memory of the polymer films were systematically studied.…”
Section: Supramolecular Chirality Of Azo-polymers Constructed By Pmentioning
confidence: 99%
“…To obtain more versatile and efficient chiral biases, scientists have investigated several chiral stimuli. For example, two types of chiral lights (circularly polarized light due to angular momentum and vortex light due to orbital angular momentum), [7][8][9][10][11][12][13][14][15] chiral nematic liquid crystals and chiral terpenes, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] chiral molecules with functional groups, 31,32 hydrodynamic swirling ow, 33,34 and biological and articial helical polymers 35 induce supramolecular chirality when achiral and optically inactive molecules and polymers are employed. These driving forces are non-covalent intermolecular weak forces including p-p, C-H/p, C-H/O, C-H/F, cation/p, dipoledipole, and van der Waals (London dispersion) interactions.…”
Section: Introductionmentioning
confidence: 99%